Analysis of selected factors related to sleep disorders on a group of older people - Bartoszek, Adrian; Szalast, Kamil; Sagan, Andrzej; Korga, Wojciech (Journal of Education, Health and Sport, 2018)
Introduction Sleep disturbances are a frequent health problem occurring among the elderly, constantly worsening with age. They affect more than 50% of older people living in a home environment and about two-thirds of those living in institutions where sleep becomes even more disturbed than at home. Problems with falling asleep or supporting sleep are reported by up to 50% of people over 60 years of age Aim Analysis of selected factors related to sleep disorders in a selected group of older people, such as age, sex, marital status, sleep time, waking up at night, time to fall asleep, the presence of naps during the day and cramps during sleep. Materials and Methods The research was conducted among 65 people aged over 60 in the Lublin Voivodeship from May to July 2018. The research method used was a diagnostic survey and the author’s questionnaire was the research tool. The level of significance was assumed at the level of p <0.05. A Chi-square conformity test was applied to the analysis of the sample. Results Sleep problems occur in 76.92% of elderly people and they related significantly more often to women, the oldest, unmarried people who wake up at least 4 times a night, need at least 60 minutes to fall asleep, nap during the day and experience leg cramps during sleep Conclusions 1. Sleep disorders are a common problem in the elderly and are of a multi-causal nature 2. Variables affecting sleep disorders in the examined group of older people are: age, sex, marital status, waking up at night, time to fall asleep, the presence of naps during the day and cramps during sleep.